Associations of physical activity with cognitive function and daily physical function among Chinese individuals with heart disease: A cross-sectional study - Xiaosheng Dong; Xiangren Yi; Ningxin Jia; Meng Ding; Yanan Zhou; Caijun Tian (Frontiers Media S.A., 2022)
BackgroundTo investigate the associations between different dimensions of physical activity (PA), cognitive function, and daily physical function in Chinese individuals with heart disease.Materials and methodsThis study included 2,792 individuals from the China Health and Retirement Longitudinal Study conducted in 2015. Physical activity (PA) was divided into vigorous PA (VPA), moderate PA (MPA), and light PA (LPA). Linear and logistic regression models were established to assess the associations among the indicators.ResultsCompared with taking no PA, MPA, and VPA at a frequency of 6-7 d/w had lower risks of impaired daily physical function (OR = 0.47, 95% CI: 0.25, 0.91; OR = 0.57, 95% CI: 0.37, 0.88) and higher cognitive function scores (β = 1.22, 95% CI: 0.42, 2.03; β = 1.08, 95% CI: 0.43, 1.73), while VPA at 3-5 d/w had lower cognitive function scores (β = −1.96, 95% CI: −3.51, −0.40). Light PA (LPA) with a duration of 30-119 min/d had a lower risk of impaired daily physical function (OR = 0.59, 95% CI: 0.36, 0.97). Moderate PA (MPA) and VPA of 30-119 min/d had higher cognitive function scores (β = 1.43, 95% CI: 0.49, 2.37; β = 1.30, 95% CI: −0.56, 2.06). The 1,800-2,999 METs had the lowest risks of impaired daily physical function and the highest cognitive function scores (OR = 0.18, 95% CI: 0.04, 0.75; β = 2.94, 95% CI: 1.67, 4.21).ConclusionModerate PA (MPA) and LPA with a frequency of 6-7 d/w and a duration of 30-119 min/d, and PA in 1,800-2,999 MET min/week were most closely related to better cognitive and daily physical function, while VPA (3-5 d/w; ≥300 min/w) may be related to low cognition, but high-quality research is necessary to prove causality.Trial registrationIRB00001052-11015.